Synthesis and evaluation of azalamellarin N and its A-ring-modified analogues as non-covalent inhibitors of the EGFR T790M/L858R mutant. (15th March 2021) - Fukuda, Tsutomu; Anzai, Mizuho; Nakahara, Akane; Yamashita, Kentaro; Matsukura, Kazuaki; Ishibashi, Fumito; Oku, Yusuke; Nishiya, Naoyuki; Uehara, Yoshimasa; Iwao, Masatomo
Graphical abstract: Abstract: Azalamellarin N, a synthetic lactam congener of the marine natural product lamellarin N, and its A-ring-modified analogues were synthesized and evaluated as potent and non-covalent inhibitors of the drug-resistant epidermal growth factor receptor T790M/L858R mutant. An in vitro tyrosine kinase assay indicated that the inhibitory activities of the synthetic azalamellarin analogues were higher than those of the corresponding lamellarins. The azalamellarin analogue bearing two 3-(dimethylamino)propoxy groups at C20- and C21-positions exhibited the highest activity and selectivity against the mutant kinase [IC50 (T790M/L858R) = 1.7 nM; IC50 (WT) = 4.6 nM]. The inhibitory activity was attributed to the hydrogen bonding interaction between the lactam NH group of the B-ring and carbonyl group of a methionine residue.